2016
DOI: 10.1002/ange.201604696
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative Silylation of Esters by Combined Nickel and Copper Catalysis for the Synthesis of Arylsilanes and Heteroarylsilanes

Abstract: An efficient nickel/copper-catalyzed decarbonylative silylation reaction of carboxylic acid esters with silylboranes is described. This reaction provides access to structurally diverse silanes with high efficiency and excellent functionalgroup tolerance starting from readily available esters. Scheme 1. Nickel/copper-catalyzed decarbonylative silylation of esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…This led to the development of a decarbonylative silylation reaction, under combined nickel and copper catalysis (Scheme 12). 49 After a series of attempts we found that silylborane compounds were efficient silicon nucleophiles due to their high reactivity and remarkable potential in copper-catalyzed transmetalations. 50 Even at high temperature, various esters can be successfully coupled with silylborane compounds to give arylsilanes or heteroarylsilanes with excellent functional group tolerance.…”
Section: Decarbonylative C−si Bond Forming Reactionsmentioning
confidence: 99%
“…This led to the development of a decarbonylative silylation reaction, under combined nickel and copper catalysis (Scheme 12). 49 After a series of attempts we found that silylborane compounds were efficient silicon nucleophiles due to their high reactivity and remarkable potential in copper-catalyzed transmetalations. 50 Even at high temperature, various esters can be successfully coupled with silylborane compounds to give arylsilanes or heteroarylsilanes with excellent functional group tolerance.…”
Section: Decarbonylative C−si Bond Forming Reactionsmentioning
confidence: 99%
“…This compound was chosen as the model substrate because of its structure, containing both ester3233343536373839 and amide group, and selective activation of amide C–N bond was very meaningful. In the presence of 10 mol% Ni(COD) 2 , 20 mol% ICy·HCl, 20 mol% NaO t Bu and 3.0 equiv K 3 PO 4 , at 130 °C under an argon atmosphere in toluene, we indeed observed the desired product 2 in 33% yield after 36 h in GC-MS (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, other uncommon coupling partners have also been evaluated. In 2016, the Rueping and Shi groups successfully reported the nickel‐catalyzed cross‐coupling of aryl carboxylates with Et 3 Si‐Bpin through the decarboxylation reaction, respectively. Very recently, the Feng group developed the first example of iron‐catalyzed silylation of aryl and alkenyl carbamates via C−O bond activation (Scheme ) .…”
Section: Iron‐catalyzed C−si Bond Formationmentioning
confidence: 99%